REGULARITIES IN DISTURBANCE:COMPARATIVE POLITICAL ANALYSIS OF THE REVOLUTIONARY WAVE 1848–1849 IN THE AUSTRIAN EMPIRE - N. S. Rozov; V. V. Tcygankov (Сравнительная политика, 2018)
The article analyzes the factors and patterns that explain the entry of some societies and the non-entry of others into the European revolutionary wave of 1848-1849, examines the causes of the various results of the revolutions. The article implements the theoretical and historical approach in macro-sociology, including shuttle movements between the General hypotheses and the systematic comparison of cases for their verifi cation and correction. In the «Spring of Nations» as a vast wave of European revolutions of 1848-1849 the imperial center (Vienna) and ethnic provinces of the Austrian Empire (Venice-Lombardy, Hungary and the Czech Republic) were taken for analysis. The factors of creating a revolutionary situation are clarifi ed and the hypothesis of «fi lling » the missing factors due to the external infl uence of revolutions in neighboring and/or highly preferred societies‒ due to the effect of the revolutionary wave is confirmed.